Manual de procedimentos do Programa Subsídio Social Básico (PSSB) - INAS - Instituto Nacional de Acção Social (2022)
O presente Manual de Procedimentos (MdP) apresenta a definição do Programa Subsídio Social Básico (PSSB), os objectivos, as componentes, os grupos-alvo, os critérios de elegibilidade, os tipos de benefícios, os mecanismos e frequência de pagamentos, a permanência de beneficiários no programa e formas de saída, a transferência de beneficiários entre componentes do programa, bem como o seu ciclo operacional. Para além dos Guiões práticos que oferecem descrições detalhadas de cada processo a ser desenvolvido por todos os actores da implementação do PSSB, o Manual tem como objectivo orientar aos intervenientes e uniformizar os procedimentos a adoptar na implementação do PSSB.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental

Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); education / educação; government policy / politica governamental

Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

Acção Social em contexto de COVID-19: Respostas e desafios em Moçambique - Siúta, Moisés; Félix, Matusse (Desafios para Moçambique, 2021, 2021)
O presente artigo tem como objectivo partilhar as medidas de resposta em contexto da COVID-19 implementadas pelo INAS, no âmbito dos programas do Governo para assistência social, tendo em conta que a eclosão da pandemia constituiu mais um factor a colocar o subsistema nacional da Segurança Social Básica (SSB) sob pressão, a fim de dar resposta a um grupo cada vez mais crescente de cidadãos moçambicanos em situação de extrema pobreza e de vulnerabilidade. O artigo está divido em cinco secções, incluindo esta introdução. São abordados os seguintes assuntos: segunda secção, a dimensão da COVID-19 e a relevância da assistência social; terceira, resposta à pandemia no âmbito dos programas do INAS; quarta, os principais desafios da acção social na resposta à pandemia; e a quinta secção apresenta considerações finais e possíveis lições
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social action / ação social; social protection / proteção social

Instituições que aprendem - Relatório para a XXVII Cimeira Ibero-Americana de Chefes de Estado e de Governo - Oliván Cortés, Raúl (XXVII Cimeira Ibero-Americana, 2020)
A pandemia da Covid-19 surgiu de súbito num momento de transição para as instituições e organizações sociais de meio mundo. Antes ainda de se ter ultrapassado a crise de confiança da última década entre os cidadãos e os governos, num momento de grande impulso das iniciativas de governo aberto e de planos de inovação e transformação digital para tornar mais democráticas e eficientes as administrações através de programas políticos encaminhados para configurar um novo contrato social, verde e digital no quadro da Agenda 2030, o coronavírus provocou um choque histórico alterando o curso do século XXI e exigindo uma aceleração de todos os processos em andamento. A complexidade e dimensão da pandemia revelou a necessidade de arquiteturas institucionais mais flexíveis, ágeis e resilientes, capazes de incorporar toda a energia civil para aprenderem com o seu talento e criatividade, dando maior protagonismo à cidadania (ativistas, empreendedores, tecido associativo, academia, makers…) não só na tomada de decisões mas também na configuração e implementação das estratégias. À medida que se afastava do centro a milhões de empregados para teletrabalhar a partir de casa, tornou-se mais poderosa a ideia de pensar nas organizações como fluxos que excedem os organigramas estáticos de lugares e pessoas. Transformar as hierarquias em redes, concebê-las como corpos sociais dinâmicos, não só alarga o seu raio de ação e conectividade externa, mas também reativa as suas forças internas, aflora as lideranças ocultas, multiplica o valor social produzido e maximiza o uso eficiente dos recursos numa época de limitações. Os laboratórios de inovação pública, social ou cidadã, ou laboratórios de governo, a par de outras formas de inovação aberta e configuração social, reivindicam-se como projetos inspiradores de uma mudança de paradigma: de instituições que ordenam para instituições que aprendem. Pensar nas organizações sob a ótica da ciência das redes e da ética dos rizomas – nós, ligações, hubs, comunidades… – deverá permitir-nos uma aproximação à complexa e subtil tarefa de configurar os ecossistemas de inovação e criatividade no âmbito público e social. Este relatório propõe um modelo denominado Hexágono da Inovação Pública (HIP) que promove uma transformação sistémica através de seis vetores (OPEN_ aberto, TRANS_ transversal, FAST_ rápido, PROTO_ modelado, CO_ colaborativo e TEC_ tecnológico) baseados nas propriedades das redes e na análise de 105 metodologias usadas pelas agências mais inovadoras do mundo. Incluem-se uma ferramenta de autodiagnóstico e o HIP-SIM, uma primeira aproximação a um software aberto para visualizar, modelar e simular a criação de ecossistemas inovadores com o qual queremos favorecer a comunidade e o debate internacional.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - tool / ferramenta; decentralization / descentralização; government policy / politica governamental; innovation / inovação

Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic: Synthesis and policy recommendations - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions, 2020)
We now proceed to bringing together the different elements of previous chapters with the aim of presenting the essence of this country study of Mozambique. In the next section, we take stock and revisit our points of departure from Chapters 2 and 3. This background work culminated in the identification of nine thematic areas, subsequently subjected to individual in-depth studies in Chapters 4–12. We outline the core findings from these studies, and present our integrated analysis of key institutional weaknesses. Next, we go a decisive step further, and analyse and discuss their proximate causes and deep factors. We end with a series of ideas for reform, as an input to national reflection, debate, and action.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; ⛔ No DOI found

Moçambique numa encruzilhada: um diagnóstico institucional: Síntese e recomendações de política - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic, 2020)
Neste capítulo reunimos os diferentes elementos dos capítulos anteriores com o objectivo de apresentar a essência deste estudo sobre Moçambique. Na secção seguinte, fazemos um balanço e revisitamos os nossos pontos de partida dos Capítulos 2 e 3. Este trabalho de fundo culminou na identificação de nove áreas temáticas, posteriormente sujeitas a estudos individuais aprofundados nos Capítulos 4-12. Descrevemos as principais conclusões destes estudos e apresentamos a nossa análise integrada das principais fraquezas institucionais. Segue-se um passo decisivo, em que analisamos e discutimos as causas imediatas e os factores profundos destas fraquezas. Finalmente, terminamos com um conjunto de ideias de reforma, como contributo para a reflexão nacional, o debate e a acção.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; ⛔ No DOI found

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

How do decision-makers use evidence in community health policy and financing decisions? A qualitative study and conceptual framework in four African countries - Kumar, Meghan Bruce; Taegtmeyer, Miriam; Madan, Jason; Ndima, Sozinho; Chikaphupha, Kingsley; Kea, Aschenaki; Barasa, Edwine (Health Policy and Planning, 2020)
Various investments could help countries deliver on the universal health coverage (UHC) goals set by the global community; community health is a pillar of many national strategies towards UHC. Yet despite resource mobilization towards this end, little is known about the potential costs and value of these investments, as well as how evidence on the same would be used in related decisions. This qualitative study was conducted to understand the use of evidence in policy and financing decisions for large-scale community health programmes in low- and middle-income countries. Through key informant interviews with 43 respondents in countries with community health embedded in national UHC strategies (Ethiopia, Kenya, Malawi, Mozambique) and at global institutions, we investigated evidence use in community health financing and policy decision-making, as well as evidentiary needs related to community health data for decision-making. We found that evidence use is limited at all levels, in part due to a perceived lack of high-quality, relevant evidence. This perception stems from two main areas: first, desire for local evidence that reflects the context, and second, much existing economic evidence does not deal with what decision-makers value when it comes to community health systems—i.e. coverage and (to a lesser extent) quality. Beyond the evidence gap, there is limited capacity to assess and use the evidence. Elected officials also face political challenges to disinvestment as well as structural obstacles to evidence use, including the outsized influence of donor priorities. Evaluation data must to speak to decision-maker interests and constraints more directly, alongside financiers of community health providing explicit guidance and support on the role of evidence use in decision-making, empowering national decision-makers. Improved data quality, increased relevance of evidence and capacity for evidence use can drive improved efficiency of financing and evidence-based policymaking.
Keywords: G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

National Action Plan on Women, Peace, and Security (2018-2022) - República de Moçambique / Republic of Mozambique Ministry of Gender, Child and Social Action (2018)
Main plan objectives include legislation re women, peace, security; integrating gender perspectives in all actions re: conflict prevention/management; guarantee participation of women in decision making, structures in peace and security processes; promoting mechanisms to secure increased recruitment, retention, promotion of women in defense, security, justice sectors; reinforce fights against all forms of violence against women/girls in armed and non-armed conflict; expanding efforts for security, physical and mental health and dignity of women and girls; securing rights of women and girl in conflict and post-conflict situations. Plan's main objectives align with the Southern Africa Development Community's Regional Strategy on women, peace, and seucirty (2018-2022).
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; government policy / politica governamental

Programa Conjunto das Nações Unidas para a Protecção Social em Moçambique 2017-2020 - Ministério do Género, Criança e Acção Social - Governo de Moçambique (Ministério do Género, Criança e Acção Social - Governo de Moçambique, 2018)
A Protecção Social é amplamente reconhecida como um conjunto efectivo de intervenções políticas para reduzir a pobreza, a vulnerabilidade a desigualdade e promover o crescimento económico inclusivo. Na última década, o sistema de Protecção Social Básica de Moçambique consolidou-se com a Estratégia Nacional de Segurança Social 2010-2014, todavia o sector ainda permanece fragmentado. A Estratégia Nacional de Segurança Social básica 2016-2024 (ENSSB II), que cobre o período de, aprovada pelo Conselho de Ministros em Fevereiro de 2016 oferece uma oportunidade única para abordar a fragmentação e alinhar melhor as partes envolvidas na materialização de um conjunto ambicioso de metas. A Estratégia tem quatro objectivos principais: 1. Incrementar o nível de consumo e resiliência da população que vive em situações de pobreza e vulnerabilidade; 2. Contribuir para o desenvolvimento do capital humano através da melhoria da nutrição, do acesso aos serviços básicos de saúde e educação do segmento da população que vive na pobreza e vulnerabilidade; 3. Prevenir e mitigar os riscos de violência, abuso, exploração, discriminação e exclusão social através dos serviços sociais e, 4. Desenvolver a capacidade institucional dos sectores governamentais que coordenam a segurança social básica. O Programa Conjunto foi estruturado em torno de um pacote coerente de intervenções, incluídas na ENSSB II e totalmente alinhadas ao Plano Operacional, em torno das 38 “Acções Estratégicas”, mas naquelas onde as agências da ONU têm mandato, capacidade de trabalho com parceiros governamentais visando fortalecer ainda mais o quadro de trabalho da Protecção Social. No decorrer do programa (2018-2019), as duas agências da ONU envolvidas (OIT e UNICEF) irão trabalhar com os parceiros a nível nacional, provincial e distrital para alcançar os seguintes resultados: 1. Até 2020, programas e políticas claras concebidos para operacionalizar a ENSSB II 2. Até 2020, evidências sólidas, advocacia e comunicação claras para as componentes principais da ENSSB II 3. Até 2020, o MGCAS tem reforçada a sua capacidade para coordenar e implementar a ENSSB II
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Estratégia Científica 2016-2015 - Instituto Nacional da Saúde - Moçambique (Instituto Nacional da Saúde - Moçambique, 2017)
A presente Estratégia Científica do Instituto Nacional de Saúde (INS) para 2016-2025 está alinhada com o Programa Quinquenal do Governo (2015-2019) e com o Plano Estratégico do Sector Saúde (PESS 2014-2019). No contexto global, a elaboração da presente Estratégia teve em conta os Objectivos de Desenvolvimento Sustentável (ODS), o Regulamento Sanitário Internacional (RSI) e a Agenda Global de Segurança Sanitária (GHSA). As principais diferenças entre a presente e anterior estratégia do INS são: 1) um horizonte temporal incrementado, sendo de 10 anos ao contrário de 5 anos na estratégia anterior; 2) uma ampliação das áreas programáticas estratégicas; 3) a inclusão de um robusto eixo estratégico de fortalecimento na área de gestão institucional. A Estratégia Científica do INS 2016-2025 está organizada em Programas e em Eixos Estratégicos. Os oito Programas desta Estratégia Científica reflectem as áreas temáticas consideradas como prioritárias. Estes Programas são: 1) Saúde e Ambiente, incluindo Saúde do Trabalhador; 2) Saúde Mental, Trauma e Violência; 3) Saúde da Mulher e da Criança; 4) Adolescente, Idoso e Outras Populações Vulneráveis; 5) Determinantes de Doenças Crónicas; 6) Doenças Transmitidas por Vectores, Negligenciadas e Zoonóticas; 7) Doenças Endémicas de Grande Impacto Sanitário; 8) Sistema de Saúde. Os cinco Eixos Estratégicos representam as funções essenciais de saúde pública. Este Eixos Estratégicos são: 1) Observatório Nacional de Saúde e Vigilância Epidemiológica; 2) Rede de Laboratórios de Referência em Saúde; 3) Pesquisa, Desenvolvimento Tecnológico e Inovação; 4) Ensino, Informação e Comunicação em Saúde; 5) Gestão e Desenvolvimento Institucional. Cada Programa e Eixo Estratégico tem um ou mais Objetivos Estratégicos e seus respectivos indicadores de impacto, cada um dos quais descreve a situação ideal que se pretende atingir a médio e longo prazo. Cada Objectivo Estratégico deve ser atingido mediante a execução de uma ou mais Acções cujo enunciado reflete num conjunto de Projectos/Actividades afins. Os Projectos são actividades com objectivos e temporalidade definidas, enquanto se denominam Actividades aquelas outras que são de carácter continuado, geralmente de gestão. Finalmente, cada Projecto/Actividade tem Produtos, Indicadores e Metas temporais e/ou quantitativas definidas. Os Projectos/Actividades temáticos encontram-se descritos em cada um dos oito programas, enquanto os Projectos/Actividades estruturantes encontram-se descritos em cada um dos cinco eixos estratégicos. A presente Estratégia Científica compreende 17 Objectivos Estratégicos, 19 Acções e 102 Projectos / Actividades.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - health services / serviços de saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Estratégia Nacional de Segurança Social Básica 2016-2024 - Governo de Moçambique (Governo de Moçambique, 2016)
a Estratégia Nacional de segurança social Básica (ENssB) 2016-2024 visa a materialização do Programa Quinquenal do governo 2015-2019, através da implementação de acções que concorrem para a redução da pobreza e da vulnerabilidade, assegurando que os resultados do crescimento da economia moçambicana beneficiem a todos os cidadãos, sobretudo os que vivem em situação de pobreza e de vulnerabilidade. A elaboração da presente Estratégia teve como base as metas definidas na Estratégia Nacional de Desenvolvimento 2015-2035, a Agenda 2063 da União Africana, os Objectivos de Desenvolvimento Sustentável, aprovados pelas Nações Unidas que, no seu conjunto, enfatizam a abordagem dinâmica e promocional da protecção social e o potencial dos instrumentos de segurança social básica para reforçar o capital humano, produtivo e social assim como a capacidade de resiliência dos agregados familiares e indivíduos mais vulneráveis. Esta estratégia pretende continuar com as acções levadas a cabo, desde a adopção da Lei de Protecção Social em 2007, para construir um sistema eficaz e eficiente de segurança social básica e apresenta uma abordagem integral para a protecção social dos grupos mais desfavorecidas da população moçambicana, definindo as linhas orientadoras para o reforço da sua capacidade de protecção contra os riscos sociais de modo que saiam da situação de vulnerabilidade numa base sustentável a longo prazo. A ENSSB 2016-2024 foi elaborada, considerando o perfil de vulnerabilidades e de riscos no país, as funções da segurança social básica e o diagnóstico da situação actual do sistema, apresentando os seguintes objectivos: 1) Reforçar o nível de consumo e a resiliência das camadas pobres e vulneráveis da população; 2) Contribuir para o desenvolvimento do capital humano, através da melhoria de nutrição e do acesso aos serviços básicos de saúde e educação das camadas pobres e vulneráveis da população; 3) Prevenir e responder aos riscos de violência, abuso, exploração, discriminação e exclusão social, através de serviços de acção social, e 4) Desenvolver a capacidade institucional para a implementação e coordenação do subsistema de segurança social básica. Para a operacionalização destes objectivos, a ENSSB 2016-2024 estrutura-se em quatro eixos de intervenção, nomeadamente: » Eixo 1: Reforço do consumo, da autonomia e da resiliência; » Eixo 2: Melhoria da nutrição e do acesso aos serviços de saúde e de educação; » Eixo 3: Prevenção e resposta aos riscos sociais; e » Eixo 4: Desenvolvimento institucional. Eixo 1: operacionaliza o primeiro objectivo da estratégia e engloba as acções que visam reforçar, no sistema de segurança social básica, as funções de compensação devido a velhice e incapacidade funcional, a redução da pobreza e da desigualdade social e a promoção da autonomia e resiliência das camadas pobres e vulneráveis da população. Prevê-se introduzir modificações no Programa Subsídio Social Básico para estabelecer os subsídios para a pessoa idosa e de incapacidade funcional. Através deste Eixo será expandido o actual Programa de Acção Social Produtiva (PASP) e reforçado o seu papel na promoção da autonomia e graduação dos seus beneficiários em situação de pobreza. Outro aspecto incluso no presente Eixo é o fortalecimento do papel da segurança social básica na resposta a choques. Eixo 2: focaliza-se nas acções que promovem o desenvolvimento do capital humano, através da melhoria da nutrição e do acesso aos serviços de saúde e educação (objectivo 2). Neste eixo estão enquadrados os subsídios para a criança. Eixo 3: diz respeito aos Serviços de Acção Social que visam prevenir e responder aos riscos sociais que afectam principalmente crianças, mulheres, pessoas idosas, pessoas com deficiência e pessoas afectadas pelo HIV e SIDA (objectivo 3). Eixo 4: Centra-se nas acções de desenvolvimento institucional (objectivo 4) requeridas para reforçar a capacidade de implementação dos primeiros três eixos a todos os níveis (central, provincial e distrital). Estão previstas na Estratégia acções para o reforço da coordenação intersectorial e a monitoria dos resultados da implementação da ENSSB 2016-2024, através do Conselho Nacional de Acção Social (CNAS). Espera-se que com a implementação da presente Estratégia sejam alcançados 3.352.515 beneficiários directos e um total de 8.274.789 beneficiários indirectos, devendo ser alocado um orçamento correspondente a 2.23% do PIB até 2024
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; government policy / politica governamental; social protection / proteção social

A framework on the emergence and effectiveness of global health networks - Shiffman, Jeremy; Quissell, Kathryn; Schmitz, Hans Peter; Pelletier, David L; Smith, Stephanie L; Berlan, David; Gneiting, Uwe; Van Slyke, David; Mergel, Ines; Rodriguez, Mariela; Walt, Gill (Health policy and planning, 2016)
Since 1990 mortality and morbidity decline has been more extensive for some conditions prevalent in low- and middle-income countries than for others. One reason may be differences in the effectiveness of global health networks, which have proliferated in recent years. Some may be more capable than others in attracting attention to a condition, in generating funding, in developing interventions and in convincing national governments to adopt policies. This article introduces a supplement on the emergence and effectiveness of global health networks. The supplement examines networks concerned with six global health problems: tuberculosis (TB), pneumonia, tobacco use, alcohol harm, maternal mortality and newborn deaths. This article presents a conceptual framework delineating factors that may shape why networks crystallize more easily surrounding some issues than others, and once formed, why some are better able than others to shape policy and public health outcomes. All supplement papers draw on this framework. The framework consists of 10 factors in three categories: (1) features of the networks and actors that comprise them, including leadership, governance arrangements, network composition and framing strategies; (2) conditions in the global policy environment, including potential allies and opponents, funding availability and global expectations concerning which issues should be prioritized; (3) and characteristics of the issue, including severity, tractability and affected groups. The article also explains the design of the project, which is grounded in comparison of networks surrounding three matched issues: TB and pneumonia, tobacco use and alcohol harm, and maternal and newborn survival. Despite similar burden and issue characteristics, there has been considerably greater policy traction for the first in each pair. The supplement articles aim to explain the role of networks in shaping these differences, and collectively represent the first comparative effort to understand the emergence and effectiveness of global health networks.
Keywords: L - english / inglês; collaboration / colaboração; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental

Programa de Acção Social Produtiva (PASP) - Documento Base - INAS - Instituto Nacional de Acção Social (Ministério da Mulher e da Acção Social, República de Moçambique, 2012)
O presente documento surge assim como um instrumento de operacionalização do PASP visando clarificar as intervenções deste programa que é mais uma contribuição da segurança social básica para os esforços do Governo no combate à pobreza, alinhando-se com outras intervenções em curso, como por exemplo, o Programa Estratégico de Redução da Pobreza Urbana (PERPU), o Fundo de Desenvolvimento Distrital (FDD) e o Programa Nacional de insumos Agrícolas. O PASP procura contribuir para a superação da insegurança alimentar crónica agravada pelos choques e riscos estruturais e impactos das mudanças ambientais, como as secas, desemprego, permitindo que os agregados familiares abrangidos tenham estabilidade económica e social. O PASP toma como alvo de intervenção os Agregados Familiares (AF) com pelo menos um elemento com capacidade para o trabalho, enfrentando altos níveis de vulnerabilidade, com prioridade para os agregados chefiados por mulheres, por pessoas com deficiências e com crianças com problemas de desnutrição, que estejam localizados nas zonas urbanas e rurais, a partir do envolvimento destes em trabalhos públicos como principal veículo para a disponibilização de transferências sociais monetárias que lhes permitam estabilizar o seu rendimento e consumo. Os mesmos agregados familiares são encorajados em seguida a se envolverem em iniciativas de geração de rendimentos através de um conjunto de acções enquadradas num processo de preparação social para a graduação. O presente documento desenvolve o modelo de intervenções do PASP, os seus objectivos, componentes, nomeadamente, trabalhos públicos com o uso da mão-de-obra intensiva e apoio ao desenvolvimento de iniciativas de geração de rendimentos, as ligações necessárias entre este. Programa e outros processos no âmbito do combate à pobreza, bem como os mecanismos de implementação, financiamento e os factores críticos de sucesso do Programa.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

PARPA II – Relatório de Avaliação de Impacto Pesquisa Sobre o Combate À Corrupção - CS Advocacia, Consultoria e Serviços (Republica de Moçambique: Ministério da Planificação e Desenvolvimento, 2009)
Este estudo enquadra‐se no âmbito dos Mecanismos e Instrumentos de Monitoria e Avaliação do Plano de Acção para a Redução da Pobreza Absoluta 2006‐2009 (PARPA II), que preconizam a preparação de um Relatório de Avaliação de Impacto (RAI). O RAI tem como objectivo sintetizar informação sobre a pobreza e a evolução de indicadores socioeconómicos e analisar esta informação com uma visão particular para atribuir causa e efeito. Como parte das prioridades do PARPA II, o combate à corrupção é um dos temas a ser abordado no RAI. Neste âmbito, o presente estudo tem como objectivo geral, avaliar o impacto das medidas adoptadas no âmbito do combate à corrupção, com enfoque nos mecanismos de controlo interno (inspecções e auditorias), relacionando com a quantidade e qualidade dos recursos humanos existentes, o desempenho e impacto do Gabinete Central de Combate à Corrupção (GCCC).
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - portuguese / português; corruption / corrupção; government policy / politica governamental

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Plano De Acção Para a Redução Da Pobreza Absoluta: 2006-09 (PARPA II) - República de Moçambique (República de Moçambique, 2006)
O Plano de Acçãoo para a Redução da Pobreza Absoluta para 2006-2009 (PARPA II) do Governo de MoÁambique tem em vista alcanÁar o objectivo de diminuir a incidÍncia da pobreza de 54% em 2003 para 45% em 2009. Este documento sucede ao PARPA I de 2001-2005 (Governo de MoÁambique, 2001), mantendo em comum as prioridades em ·reas do desenvolvimento do capital humano na educaÁ„o e sa˙de, da melhoria na governaÁ„o, do desenvolvimento das infra-estruturas b·sicas e da agricultura, do desenvolvimento rural, e de melhoria na gestão macro-económica e financeira. O presente PARPA distingue-se do anterior por incluir nas suas prioridades uma maior integração da economia nacional e o aumento da produtividade. Em particular, focaliza a atenção no desenvolvimento de base ao nÌvel distrital, na criação de um ambiente favorável ao crescimento do sector produtivo nacional, melhoria do sistema financeiro, ao florescimento das pequenas e mÈdias empresas enquadradas no sector formal, e a desenvolver ambos os sistemas de arrecadaÁ„o de receitas internas e de afectação dos recursos orçamentais.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; poverty / pobreza

PPFD/PRODER Joint Review and Strategy Proposal for the National PPFD Program Architecture - Final report - Ministry of Planning and Development - Mozambique (MÉTIER, Consultoria e Desenvolvimento, Lda, 2006)
The present report integrates the main conclusions of the three PPFD projects evaluation: PPFDNorth, PPFD-Centre and PRODER, establishing the articulation with the evolution of the political and administrative evolution and relevant for the decentralization process. Based on this analysis the report proposes the architecture of a single National PPFD Program and its main components. This report is based on the main conclusions of an extensive field work covering various provinces and districts and of the various workshops with participation of representatives of the Government at different levels, of the partners and national and international staff from the projects. It constitutes an important basis for the work of the commissions created to start the program formulations. This final report is complemented by other four partial reports: Evaluation report of the PPFD North; Evaluation report of the PPFD Centre; Evaluation report of the PRODER; and Phases 2 and 3 Report: Strategy for a single national PPFD
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; government policy / politica governamental